Habitat Suitability Modeling of Javan Slow Loris (Nycticebus javanicus) in the Forest Cluster of Gunung Halimun Salak - Giri, Misbah Satria; Munawir, Ahmad; Sundawiati, Atih; Sodahlan, Mohammad Erlan; Prasetyo, Yogi; Nugrahareni, Hermita Widi; Kurniawan, Henri; Rinekso, Albert Joni; Rahman, Dede Aulia (Institut Pertanian Bogor (IPB University), 2023)
Javan slow loris (Nycticebus javanicus) is one of the endemic wildlife on Java Island. This species owns particular characteristics, including arboreal, solitary, and nocturnal natures. The species is threatened due to habitat loss and illegal trafficking. Nevertheless, their current geographic distribution remains unclear and environmental factors impact on these species is mostly unknown. This study aims to predict the habitat suitability of javan slow loris in the Conservation Management Forest Unit area of Mount Halimun Salak Forest Group. The study employs a species distribution modeling approach using Maximum Entropy. The presence data of javan slow loris was collected from the radio-telemetry devices used in post-release monitoring. The modeling utilizes elevations, distance from the settlements, slopes, and land covered as its environment variables. The result shows that 52% of the study areas, or 54,669 ha are suitable as the habitat of N. javanicus. Since as the largest protected area on Java Island, Gunung Halimun Salak National Park is one of the natural habitats that are pivotal for this species. This study provides essential documentation for developing management strategies within protected areas. Hence, the result of the study could serve as one of the factors in the determination of animal release location in the future.